Total Pancreatectomy and Islet Cell Autotransplantation: Outcomes, Controversies and New Techniques - Radomski, Michal; Zureikat, Amer H (JOP. Journal of the Pancreas, 2015)
Chronic pancreatitis is a challenging disease; the constellation of chronic abdominal pain and metabolic derangements present unique difficulties to the treating physician. Initial treatment revolves around lifestyle modification, pain control, and management of exocrine insufficiency. In refractory cases, total pancreatectomy with islet cell auto transplantation (TP-IAT) is an option for patients with diffuse disease not amenable to subtotal pancreatectomy or a decompressive (drainage) operation. This procedure aspires to alleviate pain and avoid surgically induced brittle diabetes, a morbid complication of total pancreatectomy alone. Herein, we review the indications, optimal timing, surgical outcomes and controversies for TP-IAT, focusing on recently published reports. Image: University of Pittsburgh logo. Pittsburgh, Pennsylvania, USA